Modern weapons and military equipment for issue 3-2015 - Tišma, Mladen R. (Vojnotehnički glasnik / Military Technical Courier, 2015)
- Russia to relaunch production of Tu-160 strategic bombers; - Italian Air Force presented a new aircraft for selective and initial training; - China is developing fifth generationSTOVL fighter aircraft; - South Africa’s Denels consider restarting production improved attack helicopters; - Successful first flight of S-97 Raider helicopter; - India to modernize and arm Hawk Mk 132 trainer aircraft; - Public presentation and the first flight of An-178 transport aircraft; - Indian Air Force handed over the first modernized Mirage 2000; - Introduced a new version of the Israeli Air Force missiles i-Derby; - Talks about the possibility of equipping FA-50 light fighters with Al-Tarik precision guided munition; - Sagem offers the arming of French C-130 transport aircraft with precision guided bombs; - India has selected the A330 to develop a new AWACS; - The Brazilian navy took the first modernized AF-1 strike fighter; - Russia plans to build a new aircraft carrier.